1992
DOI: 10.1128/aem.58.12.3959-3963.1992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium chloride on the intracellular solute pools of Listeria monocytogenes

Abstract: The concentrations of intracellular solutes in Listeria nwnocytogenes were examined in cells grown at various concentrations of NaCl. At 5% NaCl, cells contained elevated concentrations of potassium and glycine betaine compared with concentrations in cells grown without NaCl. At 7.5% NaCl, cells contained increased concentrations of K+, glycine betaine, glycine, alanine, and proline. Only glycine betaine, choline, or glycine promoted growth on a solidified defined medium containing 4% NaCl; there was no growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 25 publications
0
35
0
1
Order By: Relevance
“…Accumulated compounds may include potassium ions, amino acids and their derivatives, and carbohydrates (Galinski 1995). Glycine betaine and carnitine are osmoprotectants (compounds that increase growth rates at high osmolarity) for L. monocytogenes (Patchett et al 1992;Ko et al 1994;Call and Miller 1997). Several studies have shown that these compounds have little or no growth-promoting effect at temperatures from 30°C to 37°C in the absence of osmotic stress (Beumer et al 1994;Ko et al 1994;Smith 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated compounds may include potassium ions, amino acids and their derivatives, and carbohydrates (Galinski 1995). Glycine betaine and carnitine are osmoprotectants (compounds that increase growth rates at high osmolarity) for L. monocytogenes (Patchett et al 1992;Ko et al 1994;Call and Miller 1997). Several studies have shown that these compounds have little or no growth-promoting effect at temperatures from 30°C to 37°C in the absence of osmotic stress (Beumer et al 1994;Ko et al 1994;Smith 1996).…”
Section: Introductionmentioning
confidence: 99%
“…From a food safety point of view, an obvious implication from this and other studies [1][2][3][4][5] is that use of acid, alkali and/or salt in food product processing may not be sufficient to eliminate all L. monocytogenes bacteria, as a certain number of this species will survive at very extreme pH and salt conditions. This puts good manufacturing practice to the forefront to ensure that processed, ready-to-eat food products are free of L. monocytogenes contamination.…”
Section: Discussionmentioning
confidence: 90%
“…The ability of L. monocytogenes virulent strains to tolerate and survive under harsh environmental conditions such as extreme pH (<4.0 or >9.0) and high concentration of salt (around 10%) has been well documented [1][2][3][4][5]. These external stresses often result in inhibition of L. monocytogenes growth, and once the stress factors are removed, this bacterium will resume its rapid multiplication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of osmolyte in an extract was calculated by comparison of peak intensity to that of an internal standard (50 mM alanine) whose a-carbon resonance is shown at 5 1.5 ppm. Internal concentrations were calculated by normalizing the amount of solute to cellular protein, then dividing by the cytoplasmic volume per unit protein (Patchett et al 1992). stress. lntracellular levels of glycine betaine were lower than those observed under salt stress, which is appropriate, because high levels would lead to unacceptably large turgor pressure.…”
Section: Solute Accumulation By L Monocytogenesmentioning
confidence: 99%